Evaluation of nutritional status in patients pre operatory the general surgery service of the national hospital - Salinas Medina, Silvia Angélica (2009)
The objective of the present research was to determine the nutritional status on the patients pre operative at the General Surgery Service of The National  Hospital. This research took place from April 1st to June 30th, 2005. This is a descriptive study, and trasversal non experimental design. The sample was determined through simple randomized No Probalistic sample design. It was 123 hospitalized patients attended at the General Surgery Service. Data for 18-80 years old patients, were compiled through the observational technique using an “Ad Hoc” from. The were processed with SPSS statistical program 12 version and Microsoft Excel 2003, elaborating one-dimensional and bi-dimensional frequency distribution tables, graphs and a contrast test of corresponding hypothesis. Any level of desnutrition was found in 38.2% according to de album in level, 48.8% malnourished by excess energy according to Body Mass Index (BMI) and 78.0% were at mild to moderate nutritional risk according to the Nutritional Risk Index (NRI). We concluded the patients at the General Surgery Service have a malnourished and nutritional risk according, for this population, recommending the nutritional surveillance system implementation nutritional support at patients with malnutrition before surgical